Silence superoxide dismutase 1 (SOD1): a promising therapeutic target for amyotrophic lateral sclerosis (ALS). (2nd April 2020) - Abati, Elena; Bresolin, Nereo; Comi, Giacomo; Corti, Stefania
ABSTRACT: Introduction : Amyotrophic lateral sclerosis (ALS) is a progressive and incurable neurodegenerative disorder that targets upper and lower motor neurons and leads to fatal muscle paralysis. Mutations in the superoxide dismutase 1 (SOD1) gene are responsible for 15% of familial ALS cases, but several studies have indicated that SOD1 dysfunction may also play a pathogenic role in sporadic ALS. SOD1 induces numerous toxic effects through the pathological misfolding and aggregation of mutant SOD1 species, hence a reduction of the levels of toxic variants appears to be a promising therapeutic strategy for SOD1-related ALS. Several methods are used to modulate gene expression in vivo ; these include RNA interference, antisense oligonucleotides (ASOs) and CRISPR/Cas9 technology. Areas covered : This paper examines the current approaches for gene silencing and the progress made in silencing SOD1 in vivo . It progresses to shed light on the key results and pitfalls of these studies and highlights the future challenges and new perspectives for this exciting research field. Expert opinion : Gene silencing strategies targeting SOD1 may represent effective approaches for familial and sporadic ALS-related neurodegeneration; however, the risk of off-target effects must be minimized, and effective and minimally invasive delivery strategies should be fine-tuned.